2022
DOI: 10.1007/s00415-021-10942-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glutamate and decreased glutamine levels in the cerebrospinal fluid of patients with MELAS syndrome

Abstract: Background Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome is a genetically heterogeneous disorder caused by mitochondrial DNA (mtDNA) mutations in the MT-TL1 gene. The pathophysiology of neurological manifestations is still unclear, but neuronal hyperexcitability and neuron-astrocyte uncoupling have been suggested. Glutamatergic neurotransmission is linked to glucose oxidation and mitochondrial metabolism in astrocytes and neurons. Given the relevance of neuron-astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…This study demonstrates that high‐dose glutamine oral supplementation for 12 weeks significantly reduces CSF glutamate and increases CSF glutamine levels in patients with MELAS syndrome. However, the CSF levels of alanine, branched‐chain amino acids (BCAAs) and lactate, which were significantly higher before treatment with glutamine [13], did not change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study demonstrates that high‐dose glutamine oral supplementation for 12 weeks significantly reduces CSF glutamate and increases CSF glutamine levels in patients with MELAS syndrome. However, the CSF levels of alanine, branched‐chain amino acids (BCAAs) and lactate, which were significantly higher before treatment with glutamine [13], did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach was completely different. It was hypothesized that significantly higher CSF glutamate levels and lower CSF glutamine levels found in patients with MELAS syndrome might reflect that the glutamate–glutamine cycle is altered due to insufficient energy production to maintain glia–neuron coupling [13]. This quasi‐experimental study showed that glutamine supplementation helps restore equilibrium, reducing glutamate and increasing glutamine in CSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, increased amino acid levels, including glutamate levels, are consistent with a compensatory response to the primary MELAS OXPHOS defect [ 39 , 50 ]. A recent study aimed to assess glutamate and glutamine levels in plasma and cerebrospinal fluid in MELAS patients showed an elevated glutamate level in the CSF but not in the plasma [ 51 ] and in contrast, the CSF glutamine level was lower than controls [ 51 ]. These data raise the question of glutamate-glutamine balance in the pathophysiology of MELAS.…”
Section: Discussionmentioning
confidence: 99%